2017
DOI: 10.1111/eip.12475
|View full text |Cite
|
Sign up to set email alerts
|

Sensory characteristics of youth at clinical high risk for psychosis

Abstract: Young people with CHR demonstrate active avoidance, heightened sensitivity, reduced seeking, and reduced registration of sensations in everyday life compared to typical peers. This pattern of differences may be a valuable marker for identifying individuals who are at high risk for developing a psychotic illness, and may also inform interventions designed to prevent or minimize the illness process and accompanying dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…These atypical results are consistent with those of an adult South African substance-using sample, 3 and with multiple studies examining the sensory processing patterns associated with a range of mental and physical health conditions. 1 , 2 , 9 , 11 , 15 20 , 40 , 41…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These atypical results are consistent with those of an adult South African substance-using sample, 3 and with multiple studies examining the sensory processing patterns associated with a range of mental and physical health conditions. 1 , 2 , 9 , 11 , 15 20 , 40 , 41…”
Section: Discussionmentioning
confidence: 99%
“…Norms exist for Dunn's four sensory patterns, with evidence that scores outside the norm are associated negatively with daily functioning and quality-of-life, 2,15 resilience, 1 as well as engagement in community participation and subsequent recovery-orientated outcomes. 16 More atypical patterns have also been linked with physical and mental health conditions, including psychosis, 17 post-traumatic stress disorder (PTSD), 18 depression, anxiety, and obsessive-compulsive disorder, 10,18 interpersonal difficulties 17 and pain. 17,19,20 Studies with adult clinical and non-clinical AOD samples, although limited, have revealed that low registration, sensation avoiding, and sensory sensitivity patterns differ significantly from the general population.…”
Section: Sensory Profile Patterns In Research Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensory abnormalities, beyond hallucinations, are common in patients with Schizophrenia, though they are often ignored in practice (Javitt & Freedman, 2015). For instance, studies using the Sensory Profile (Dunn, 1997) have reported abnormally high scores in sensory sensitivity, sensation avoiding, and low registration in SCHZ (e.g., Brown, Cromwell, Filion, Dunn, & Tollefson, 2002;Halperin, 2018;McGhie & Chapman, 1961;Melle et al, 1996;Muntaner et al, 1993;Parham et al, 2017;Pfeiffer et al, 2014). Other studies have reported behavioral sensory abnormalities, such as hyperacusis (sounds seeming louder than they physically are), decreased auditory memory, misperception and distortion of sounds and visual stimuli, decreased acuity in processing dim, rapidly presented, or moving objects, increased pain thresholds, impaired two-point discrimination, and odor discrimination deficits (see Javitt, 2009 andFreedman, 2015 for reviews).…”
Section: Abnormal Sensorymentioning
confidence: 99%
“…This population also experiences high rates of co-occurring mental health and medical issues [13]. Studies of people with post-traumatic stress disorder [11], mood and affect disorders [14,15], pain [16] and psychosis [17] showed atypical sensory processing. Cognitive functioning may also influence regulation and people with AOD issues experience significant rates of memory and attention impairment, acquired brain injury and neurodevelopmental disorders [17,18].…”
mentioning
confidence: 99%